Clustering entrepreneurship aspirations: innovation, growth and international orientation of activities - Nunes, Alcina (2014)
It is sometimes argued that nations differ in their underlying entrepreneurial spirit. So, in recent years, more researchers started being interested in the analysis of entrepreneurship across regions. Associated with entrepreneurship comes the concept of innovation. Innovation allows the creation of new firms and/or ensures the survival of the existing ones, and in both cases, generates growth. Applying the statistical technique of cluster analysis to a country dataset gathered by the Global Entrepreneurship Monitor (GEM) this paper groups countries into four clusters regarding their entrepreneurial activity and the aspirations of national entrepreneurs concerning innovation, business growth and international orientation of their activities. This is particularly important not only because the achievement of a relevant national entrepreneurship rate depends on the social and economic business environment but also because it is not known if there are particular regions where the entrepreneurial activity is characterised by special patterns of entrepreneurship aspirations.